Protein content of Spirulina sp. Cultured Using a Combination of Urea and TSP Fertilizers - Sutianto Pratama Suherman; Bunajir Bunajir; Hasim Hasim; Sulastri Arsad (Department of Aquaculture, 2022)
This study aims to determine the effect of the combined use of Urea and TSP fertilizers on the Protein content of Spirulina sp. This research was conducted for 10 days at the Center for Brackish Water Aquaculture (BPBAP) Takalar. The method used in this study is an experimental design with Completely Randomized Design (CRD) using 4 treatments with 3 replications, namely Treatment A (0.4 g/l Urea + 0.008 g/l TSP), B (0.5 g/l Urea + 0.010 g/l TSP), C (0.6 g/l Urea + 0.012 g/l TSP) and D (0.4 g/l Urea + 0.008 g/l TSP). The data obtained were analyzed using descriptive analysis method. The results showed that the use of a combination of Urea and TSP fertilizers could have an effect on the protein content of Spirulina sp. with the highest protein content obtained in treatment C of 34.33%.